PENGELOLAAN BISNIS PERHOTELAN SYARIAH - Muhammad Riza Hafizi; Dyah Sulistiyo Rimbodo (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2019)
AbstractThe government has made regulations regarding the regulation of Sharia Hotels reviewed through the National Sharia Council-Indonesian Ulama Council concerning Minister of Tourism and Creative Economy Regulation Number 2 of 2014. Hotel Jamrud Syariah, one of the hotels in Central Kalimantan which is a family business managed with three aspects namely products, service and management. The purpose of the study was to analyze how the management of the sharia hotel business at the Islamic Jamrud Hotel. This research is a field research using descriptive qualitative research methods. The subjects of this study are the owners, employees and visitors of the Sharia Jamrud Hotel in Pangkalan Bun. Data analysis techniques using collection data, data reduction, data display, and conclusion drawing. The results of this study indicate that the management of the Pangkalan Bun Syariah Jamrud hotel has been well managed. Then the management of sharia business hotels at the Islamic Jamrud Hotel has fulfilled the absolute criteria if viewed from the National Sharia Council-Indonesian Ulema Council regarding Minister of Tourism and Creative Economy Regulation Number 2 of 2014.Keywords: Products, Services, ManagementAbstrak  Pemerintah telah membuat peraturan tentang regulasi Hotel Syariah ditinjau melalui Dewan Syariah Nasional-Majelis Ulama Indonesia mengenai Peraturan Menteri Pariwisata dan Ekonomi Kreatif Nomor 2 Tahun 2014. Hotel Jamrud Syariah, salah satu hotel di Kalimantan Tengah yang merupakan bisnis keluarga yang dikelola dengan tiga aspek yaitu produk, pelayanan dan pengelolaan. Tujuan penelitian adalah untuk menganalisis bagaimana pengelolaan bisnis perhotelan syariah pada Hotel Jamrud Syariah. Penelitian ini merupakan penelitian lapangan menggunakan metode penelitian kualitatif deskriptif. Adapun subjek penelitian ini adalah pemilik, karyawan dan pengunjung Hotel Jamrud Syariah Pangkalan Bun. Teknik analisis data menggunakan data collection, data reduction, data display, dan conclusion drawing. Hasil dari penelitian ini menunjukkan bahwa pengelolaan hotel Jamrud Syariah Pangkalan Bun sudah dikelola secara baik. Kemudian pengelolaan perhotelan bisnis syariah pada Hotel Jamrud Syariah sudah memenuhi kriteria mutlak jika ditinjau dari Dewan Syariah Nasional-Majelis Ulama Indonesia mengenai Peraturan Menteri Pariwisata dan Ekonomi Kreatif Nomor 2 Tahun 2014.Kata Kunci: Produk, Pelayanan, Pengelolaan